2001
DOI: 10.1074/jbc.m010384200
|View full text |Cite
|
Sign up to set email alerts
|

MAPK/ERK Overrides the Apoptotic Signaling from Fas, TNF, and TRAIL Receptors

Abstract: The tumor necrosis factor (TNF), Fas, and TNF-related apoptosis-inducing ligand (TRAIL) receptors (R) are highly specific physiological mediators of apoptotic signaling. We observed earlier that a number of FasR-insensitive cell lines could redirect the proapoptotic signal to an anti-apoptotic ERK1/2 signal resulting in inhibition of caspase activation. Here we determine that similar mechanisms are operational in regulating the apoptotic signaling of other death receptors. Activation of the FasR, TNF-R1, and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
222
3
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(238 citation statements)
references
References 69 publications
10
222
3
3
Order By: Relevance
“…Besides, SIP has been found to interact with ERK1/2 and downregulate ERK activity (Kilanczyk et al, 2009). Furthermore, suppression of the ERK-involved pathway sensitizes cancer cells to apoptosis (Tran et al, 2001;Wu et al, 2004) and a series of inhibitors targeting ERK pathway have been identified as potential anti-cancer drugs (Daouti et al, 2009). It has also been shown that SIP serves as a molecular bridge between Siah-1 and Skp1 proteins, and forms a ubiquitin ligase complex together with Ebi and in turn promotes b-catenin degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, SIP has been found to interact with ERK1/2 and downregulate ERK activity (Kilanczyk et al, 2009). Furthermore, suppression of the ERK-involved pathway sensitizes cancer cells to apoptosis (Tran et al, 2001;Wu et al, 2004) and a series of inhibitors targeting ERK pathway have been identified as potential anti-cancer drugs (Daouti et al, 2009). It has also been shown that SIP serves as a molecular bridge between Siah-1 and Skp1 proteins, and forms a ubiquitin ligase complex together with Ebi and in turn promotes b-catenin degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, especially the classical mitogen-activated protein kinase (MAPK) signaling pathway has been implicated as a dominant negative regulator of DR-mediated apoptosis. We have observed that MAPK/extracellular signal-regulated kinase (ERK) signaling potently modifies FasR responses (34,35) and found indications that it is involved in regulating also TRAIL-R responses (36). We have also shown that MAPK/ERK signaling from the TCR is able to protect T cells from FasR-mediated apoptosis (37) before they commit activation-induced cell death (AICD).…”
mentioning
confidence: 86%
“…It is well known that several cell lines can be sensitized to DRmediated apoptosis by pretreatment with protein synthesis inhibitors (36). This raises the possibility that the MAPK/ERK-mediated effect could be protein synthesis dependent.…”
Section: The Mapk/erk-mediated Protection Is Independent Of Protein Smentioning
confidence: 97%
“…HMBA downregulates NFκB pathway is another important pathway involved in cell survival [21][22][23] and has been shown to activate NFκB responses by activation of p90 Rsk. [24][25][26][27] In an effort to understand the mechanism of action of HMBA, we investigated its effect on the NFκB pathway.…”
Section: N O T D I S T R I B U T Ementioning
confidence: 99%